Engagement of CD300c by a Novel Monoclonal Antibody Ameliorates Behavioral Deficits in a 5xFAD Mouse Model of Alzheimer’s Disease - Suin Lee; Chang Ki Lim; Jongyeob Kim; Joon Kim; Hee Kyung Jin; Jae-sung Bae; Jae-Won Jeon (Biomedicines)
Background: Current treatment modalities for Alzheimer’s disease (AD), which is characterized by the accumulation of amyloid β (Aβ), have limitations with regard to their efficacy and safety, posing significant challenges for advances in healthcare. However, recent studies indicated that AD can be treated using monocyte-derived macrophages (MDMs). Reportedly, the protein CD300c regulates monocyte differentiation, indicating that targeting CD300c could offer a treatment for AD. Methods: To confirm this, we developed CB201, a fully human anti-CD300c antibody, and demonstrated its strong and specific binding to CD300c using surface plasmon resonance and binding ELISAs. Results: Treatment of THP-1 and human peripheral blood mononuclear cells with CB201 led to increased levels of pro-inflammatory cytokines and the differentiation of macrophages to MDMs. Moreover, the CB201-differentiated macrophages expressed cytokines and chemokines in a pattern that alleviates AD symptoms. In a 5xFAD mouse model, CB201 treatment improved memory and behavior in both the early and late stages of AD and reduced cerebral Aβ plaque load. Conclusions: These results indicate that CB201 promotes the differentiation of macrophages to MDMs and modulates AD-related inflammatory responses, thereby ameliorating the pathological features of AD. These findings identify CD300c as a potential therapeutic target for AD and indicate that CB201 is a promising candidate for its treatment.